2022
DOI: 10.1016/j.crfs.2021.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Compositional characteristics of dairy products and their potential nondairy applications after shelf-life

Abstract: Many dairy products are discarded and useless after end of shelf-life, which causes economic and environmental challenges. The objective of this study was to study the compositional characteristics of some dairy products before and after shelf-life, and develop a process to utilize those dairy products after end of shelf-life in non dairy applications (cosmetic cream and soap). Several dairy products, such as sterilized milk, yogurt, soft cheese, hard cheese, cream, and butter were collected from markets in Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Our results are also consistent with a previously published study by the other researchers on the composition of milk and other dairy products [13]. Tey found that there were no noticeable changes in fat, protein, acidity, and lactose contents as well as total material count of the sterilized milk before and after the expiration date [13].…”
Section: Homogeneoussupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are also consistent with a previously published study by the other researchers on the composition of milk and other dairy products [13]. Tey found that there were no noticeable changes in fat, protein, acidity, and lactose contents as well as total material count of the sterilized milk before and after the expiration date [13].…”
Section: Homogeneoussupporting
confidence: 93%
“…Tis can be achieved by policy changes allowing longer time between pasteurization and expiration, by industry initiatives to standardize the nomenclature of expiration date, or by consumer education. In addition, expired dairy products can be used to make soap and cosmetic products [13], further reducing waste.…”
Section: Homogeneousmentioning
confidence: 99%
“…Dairy products also represent a great group of food products with an extensive variety and geographic distribution [ 130 ], but with limited shelf-life due to spoilage microorganisms’ growth [ 131 ], which degrade milk components causing an unsatisfactory quality of the product [ 132 ]. Therefore, there is an increasing need to protect and prolong the shelf-life of such products.…”
Section: Application and Effects Of Nisin Incorporated Packaging Mate...mentioning
confidence: 99%
“…Consumption of inter-species milk is common, particularly among humans, who consume other mammalian milk [6]. Milk is a good medium for the growth of microorganisms [7], especially pathogenic bacteria such as Staphylococcus aureus, Escherichia coli, and Salmonella sp [8], [9]. Microorganisms in raw milk can thrive if stored at room temperature [10], [11].…”
Section: Introductionmentioning
confidence: 99%